The Influence of English Language Teaching on the Development of Multicultural Competence Among Higher Education Students - Budianto, Sekar Mayang Fitria; Maghfiroh, Ana; Mustikawati, Diyah Atiek; Indriastuti, Niken Reti; Asiyah, Siti (Universitas Muhammadiyah Surakarta, 2023)
In an era of globalization, English proficiency is essential for effective communication among diverse cultural groups, making English for Multicultural Competence (EMC) a vital component of English language education. This research aims to (1) investigate the effectiveness of EMC teaching among higher education students, and (2) explore the impact of English language teaching on developing multicultural competence in higher education students. This study employs a mixed-methods approach, integrating quantitative data from a Likert scale questionnaire and qualitative data from semi-structured interviews. Participants include Indonesian students studying abroad and those engaged in overseas exchange programs. The results indicate a positive correlation between English proficiency and multicultural competence, highlighting that students who actively participate in multicultural activities and utilize English in their campus life develop better intercultural communication skills. Challenges such as time constraints and limited interaction with international peers were also identified. Overall, the results affirm the significance of EMC programs in promoting cultural sensitivity, critical thinking, and empathy among students, ultimately preparing them for success in the global workforce. This research provides insights into effective practices and the impact of English language teaching on enhancing multicultural competence in higher education contexts.